Positron Emission Tomography Imaging of Tumor Cell Metabolism and Application to Therapy Response Monitoring - Challapalli, Amarnath; Aboagye, Eric O. (Frontiers in Oncology, 2016)
Cancer cells do reprogramme their energy metabolism to enable several functions such as generation of biomass including membrane biosynthesis, and overcoming bioenergetic and redox stress. In this article we review both established and evolving radioprobes developed in association with positron emission tomography (PET) to detect tumor cell metabolism and effect of treatment. Measurement of enhanced tumor cell glycolysis using 2-deoxy-2-[18F]-fluoro-D-glucose is well established in the clinic. Analogues of choline including [11C]-choline and various fluorinated derivatives are being tested in several cancer types clinically with PET. In addition to these, there is an evolving array of metabolic tracers for measuring intracellular transport of glutamine and other amino acids or for measuring glycogenesis, as well as probes used as surrogates for fatty acid synthesis or precursors for fatty acid oxidation. In addition to providing us with opportunities for examining the complex regulation of reprogrammed energy metabolism in living subjects, the PET methods open up opportunities for monitoring pharmacological activity of new therapies that directly or indirectly inhibit tumor cell metabolism.